Correction to: A new approach based on convolutional neural network and feature selection for recognizing vehicle types(Iran Journal of Computer Science, 10.1007/s42044-022-00125-6) - Doğan, Gürkan; Ergen, Burhan (Springer International Publishing, 2023)
The sentence beginning 'Bu nedenle bu …' in this article should have read 'Therefore, in this study, a combination of OMobileNetv1, OMobileNetv2, ONASNetMobile CNN methods for feature extraction, LSVC method for feature selection and SVM method for classification is proposed.' The original article has been corrected. © The Author(s), under exclusive licence to Springer Nature Switzerland AG 2022.